Praktik pekerjaan sosial berbasis masyarakat (Studi: Penanganan masalah anak putus sekolah) - Aris Tristanto; Yunilisiah Yunilisiah; Tamrin Bangsu (Altruis: Journal of Community Services, 2022)
The community service activities focused on solving the problem of school dropouts in RW 10 RT 01 Cisurupan Village, Bandung City. The model chosen in this community service involves all segments of society. The methods and techniques used in this activity refer to community social work practices. The result of assessment showed that the problems faced by parents were the lack of knowledge about how to motivate children to learn. The intervention of this activity was carried out in the form of psychoeducation and learning assistance. The main purpose of psychoeducation is to provide understanding to parents on how to motivate children to learn. The result showed an increase in willingness and enthuasism for learning in children.